Empowering women in business through improved chicken in Tanzania - Ojwang, Sylvester; Jumba, Humphrey; Galiè, Alessandra; Jasada, Ijudai; Jeremiah, Adolf; Karugia, Joseph (2025)
Women farmers in developing countries face major barriers to engaging in livestock businesses, including limited access to quality livestock seed, veterinary services, and markets—challenges mostly created by restrictive gender norms. The International Livestock Research Institute (ILRI)-led Women in Business (WiB) project is addressing these barriers by engaging young women veterinary graduates as vendors to deliver improved chicken breeds and animal health services to remote women farmers while linking them to urban markets. Partnering with Shujaaz Inc, a private social media company, ILRI is implementing Gender Transformative Approaches (GTAs) via social media campaigns—#BintiShujaaz (heroine)—and talk shows on a local radio station to challenge some of the inequitable norms behind women’s disadvantage. The WiB model has empowered both vendors and women farmers, leading to improved incomes, nutrition, and gender equality. It is now being adopted by government and private sector actors and scaled to other livestock value chains (such as dairy) and other geographies, including Dodoma in Tanzania, Zambia, with plans for Ethiopia, South Sudan, Lesotho, Kenya, and Uganda.